Single-phase Mail Survey Design for Rare Population Subgroups. Issue 4 (November 2016) - Brick, J. Michael; Andrews, William R.; Mathiowetz, Nancy A.
Although using random digit dialing (RDD) telephone samples was the preferred method for conducting surveys of households for many years, declining response and coverage rates have led researchers to explore alternative approaches. The use of address-based sampling (ABS) has been examined for sampling the general population and subgroups, most often using mail or invitations to web surveys. For surveying rare groups, these studies often involve multiple phases to identify eligible population members and then collect responses. We describe a new approach for surveying rare subgroups using ABS with a single-phase mail survey. The study incorporates a new method for using a list frame with the ABS frame to increase the yield of the subgroup of interest while avoiding a potential bias inherent in many dual-frame survey designs. The findings suggest that the new approach is both efficient and effective for identifying and measuring a rare population.